Silicon Photomultipliers for Neutrino Telescopes - Diego Real; David Calvo (Universe, 2023)
Neutrino astronomy has opened a new window to the extreme Universe, entering into a fruitful era built upon the success of neutrino telescopes, which have already given a new step forward in this novel and growing field by the first observation of steady point-like sources already achieved by IceCube. Neutrino telescopes equipped with Silicon PhotoMultipliers (SiPMs) will significantly increase in number, because of their excellent time resolution and the angular resolution, and will be in better condition to detect more steady sources as well as the unexpected. The use of SiPMs represents a challenge to the acquisition electronics because of the fast signals as well as the high levels of dark noise produced by SiPMs. The acquisition electronics need to include a noise rejection scheme by implementing a coincidence filter between channels. This work discusses the advantages and disadvantages of using SiPMs for the next generation of neutrino telescopes, focusing on the possible developments that could help for their adoption in the near future.